2022
DOI: 10.1002/admi.202201237
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Free Scalable Fabrication of Linearly Periodic Microstructures by Controlling Ribbing Defects Phenomenon in Forward Roll Coating for Multifunctional Applications

Abstract: developing multifunctional surfaces with unique capabilities, including superhydrophobicity, [1,2] self-cleaning, [3,4] anti-icing, [3,5] anti-biofoulin, [6,7] biological sensors, [6] and radiative cooling. [6,8] For example, Namib Desert beetles use the superhydrophobicsuperhydrophilic micropatterned skin to harvest water from fog. [12][13][14] Plants such as lotus utilize microstructures on leaves to influence wetting behavior and enable self-cleaning. [12,15] Sharks' unique skin morphology augments the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 95 publications
2
29
0
Order By: Relevance
“…Finally, the samples' water contact angles were measured by the low-bond axisymmetric drop shape analysis plugin provided by the ImageJ software. The surface energy calculation was based on Fowke's model and the Owens-Wendt model (SI.9) 20 .…”
Section: Liquid Contact Angle Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the samples' water contact angles were measured by the low-bond axisymmetric drop shape analysis plugin provided by the ImageJ software. The surface energy calculation was based on Fowke's model and the Owens-Wendt model (SI.9) 20 .…”
Section: Liquid Contact Angle Measurementmentioning
confidence: 99%
“…1(b) and Video (for presenting convenience, 15 vol% Al2O3/PDMS (relative low viscosity) and low roller speed are utilized). Our previous simulation research demonstrated that surface energy γ, viscosity η, roller radius R, roller gap d, and roller speed U had strong correlations with the pressure gradient in the flow direction, which directly led to the formation of the spike "defects" 20 . To demonstrate the effects of η, U, γ, and R/d on the final spikes' peak periodicity (pspike), parametric experiments are conducted with U ranging from 20 rpm to 100 rpm, and R/d from 100 to 320.…”
Section: Materials' Fabrication and Optical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the performance and cost were limited by the metal substrate . The common ribbon and spike defects in traditional roll-to-roll manufacturing inspired researchers to develop a novel scalable way to fabricate periodical microstructures. Specifically, the positive pressure gradient generated in the downstream meniscus sows the seeds of the spike “defects” on the surface. These defects can be robustly kept when the material’s rheological properties are modified by adding nanoparticles. In this situation, the defects’ peak pitch length is correlated to material properties (i.e., surface energy and viscosity) and fabrication parameters (i.e., roller radius, roller gap, and roller speed). The optimized spike microstructures for high cooling performance can be obtained by manipulating the embedded nanoparticles and fabrication parameters.…”
mentioning
confidence: 99%
“…Our previous simulation research demonstrated that surface energy γ, viscosity η (or complex viscosity η*), roller radius R, roller gap d, and roller speed U were strongly correlated to the pressure gradient in the flow direction, which directly led to the formation of the spike "defects". 23 . The parametric roll-to-roll experiment results demonstrate that the higher η (higher particle content), U, and R/d would lead to a smaller p spike as shown in Figure 3g and Table S5.…”
mentioning
confidence: 99%